Indícios de apropriação do conceito de função por meio da aprendizagem da docência: uma proposta formativa no clube de matemática ensino médio - Silva, Mayline Regina (2023)
This text presents the synthesis of a pedagogical investigation conducted with female Mathematics teachers in the initial training phase. The object of the research is the learning of teaching through the process of appropriation of mathematical knowledge, precisely the concept of function, to understand the transformations that can be facilitated by the Expansive Learning Cycle, allowing an in-depth analysis of the essence of this concept and the appropriation of the theoretical thinking associated with it. The methodological approach is based on Historical-Dialectical Materialism and uses a structured formative experiment supported by the Historical-Cultural, Activity, and Teaching Guiding Activity Theories. The central question of the research focuses on how teachers in initial training understand teaching based on the process of appropriating the concept of function. The hypothesis explored is related to the perspective that the appropriation of mathematical knowledge can influence the learning of teaching through a pedagogical approach linked to its five principles: the understanding of the school as a space for the appropriation of culture, the recognition of the teacher as the subject of training processes, pedagogical intentionality as an essential element in the organization of teaching, sharing as a fundamental principle for understanding pedagogical activity, and mathematical knowledge as a promoter of human development. The study covered two school years, 2021 and 2022, during which training meetings were held that emphasized studies, planning, and evaluation of each learning cycle. In this context, the research focuses on the importance of understanding the individual needs of future teachers throughout their development through the appropriation of culture. The investigative process promoted in-depth discussions, sharing of ideas, construction of meanings, and deconstruction of the barriers imposed on disseminating mathematical knowledge in its social imposition. Recognition of, and active participation in, a training environment such as the High School Math Club underlines the need to organize scientific knowledge in favor of its cultural appropriation, both by teachers and students in elementary and secondary education.